Mind the Gap: Analyzing Discrepancies between Diversity Management Best Practices and Real-World Implementation - Shahi, Rozy; Shrestha, Suraj; Shahu, Usha (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2024)
Purpose: Diversity management plays a crucial role in the growth and success of organizations. This paper aims to explore the concept of diversity, its various types, associated benefits, relevant theories, and its implications worldwide. Additionally, it examines the existing gap between expectations and reality in implementing best practices for diversity management Methodology: To provide a comprehensive understanding, this study conducts a thorough review of quantitative and qualitative research, as well as theoretical studies published in renowned journals. The researchers extensively analyze research articles, management books, newspaper articles, and constitutional documents from different countries, adhering to established search inclusion criteria. Findings: The paper emphasizes the significance of effective diversity management and delves into the vast disparity between the conceptualization of diversity and its practical implementation. It also highlights that the theories surrounding diversity may not be fully realized when put into practice, potentially hindering the desired outcomes. Furthermore, the study uncovers numerous loopholes in the global understanding, examination, and implementation of diversity, even within constitutional frameworks. This study contributes to the field of contemporary management by shedding light on the Diversity Management. It significantly enhances our knowledge of diversity and the factors that influence its effective management, offering valuable insights for organizations seeking to foster inclusivity and leverage the benefits of diverse workforces. DOI: https://doi.org/10.69476/sdpr.2024.v01i01.005